Política social e inseguridad. El caso de Apatzingán, Michoacán - Chávez Orihuela, Amalia (Universidad Michoacana de San Nicolás de Hidalgo, 2017)
The present thesis had as main objective to analyze the causes of violence and crime in the municipality of Apatzingán, Michoacán from a perspective of the institutional decomposition. Based on empirical data and a literature review, we observed the presence of multidimensional factors that explain violence and crime in this region of Michoacán. Therefore, it is necessary that the Mexican State design public policies from a multidimensional perspective that does not emphasize only the police or military aspects, but incorporates elements such as cultural, social and educational elements. Likewise, it is important to achieve greater legitimacy of the institutions that regulate social coexistence as an indirect way of reducing the environment of crime.

La presente tesis tuvo como objetivo central analizar las causas de la violencia y el crimen en el municipio de Apatzingán, Michoacán desde una perspectiva de la descomposición institucional. A partir de datos empíricos y de una revisión bibliográfica, se observó la presencia de factores multidimensionales que explican la violencia y el crimen en esta región de Michoacán. Por lo tanto, es necesario que el Estado mexicano diseñe políticas públicas a partir de una perspectiva multidimensional que no enfatice únicamente los aspectos policiacos o militares, sino que incorpore elementos tales como elementos culturales, sociales y educativos. Así mismo, es importante lograr una mayor legitimidad de las instituciones reguladoras de la convivencia social como una manera indirecta de reducir el entorno del crimen.
Facultad de Derecho y Ciencias Sociales. Maestría en Derecho
Keywords: info:eu-repo/classification/cti/5; FDCS-M-2017-0289; Humanidades; Crimen; Delincuencia; Caballeros templarios; Delincuencia; http://bibliotecavirtual.dgb.umich.mx:8083/xmlui/handle/DGB_UMICH/784